Fuzzy logic controller for half car active suspension system - Basari, A.A.; Nawir, N.A.A.; Mohamad, K.A.; Ng, X.Y.; Khafe, A.M. (Faculty of Electronic and Computer Engineering (FKEKK), Universiti Teknikal Malaysia Melaka (UTeM), 2018)
This work presents the MATLAB/Simulink simulation results of half car active suspension system controlled by the fuzzy logic controller. The half car model consists of one front and rear wheel. Firstly, a mathematical model of the suspension system is developed. Based on the developed mathematical model, the fuzzy logic controller for the system is designed. The input to the controller is the vertical displacement and velocity of the front body of the vehicle. The membership function of these two variables is adjusted accordingly so that the output, i.e., the car body acceleration, the deflection of the wheels and other output are better than that of the passive suspension system. The results clearly show that all of the active suspension system output has improved when compared to that of the passive system.